PENINGKATAN HIGIENE MENSTRUASI MELALUI PEMBERIAN PENDIDIKAN KESEHATAN - Mariene Dolang (STIKES Pasapua Ambon, 2019)
Introduction : Menstruation problems are problems that often occur in adolescents. During menstruation, blood vessels in the uterus are susceptible to infection so teenagers are expected to be able to maintain the cleanliness of the reproductive organs to avoid infection. One appropriate way to increase knowledge and change attitudes and actions is by providing health education. This study aims to determine the knowledge, attitudes, and actions about menstrual hygiene before and after health education is given about menstrual hygiene. Method: This research is a Pre Experiment research with One Group Pratt Posttest design. The population in this study were all students of SMP Negeri 1 Masohi. The sample in this study were 35 female students of SMP Negeri 1 masohi who had menstruated. The data collected was obtained from direct interviews of respondents selected as samples using a list of questions that had previously been compiled. Data processing and analysis is done by computerization and presented in the form of frequency distribution and cross tabulation by using the Indepentent T Test if the data is normally distributed and if the data is not normally distributed the Wilcoxon test is used with a significance level of p <0.05. Result: The results of this study indicate that there is an effect of the provision of health education to knowledge (p = 0,000, Mean Pre = 20,03, Mean Post = 24,86), attitudes (p = 0,000, Mean Pre = 54,57, Mean Post = 60,00), and actions (p = 0,000, Mean Pre = 4,63, Mean Post = 5,77) about menstrual hygiene to students at SMP Negeri 1 Masohi. Conclution : There is an influence of providing health education on knowledge, attitudes, and actions regarding menstrual hygiene . This research suggests that the school can more routinely provide information related to reproductive health, especially menstrual hygiene to students.